The Relationship of Hospital Cost, Service Quality and Patient Satisfaction (Jurnal Ilmu Kesehatan Masyarakat, 2019)
Customer satisfaction becomes very important to determine the success of service companies. One way to survive in the healthcare industry today is to create customer satisfaction through improved service quality. Hospital cost is an indicator for patients to utilize health services. This study aims to analyze the relationship of hospital cost and service quality with patient satisfaction. This study used analytic survey with a cross-sectional study design. The sample of this study is the general patient who used inpatient and outpatient installation of Bhayangkara Hospital in Palembang as many as 117 patients. The sampling technique used systematic random sampling. Analysis of statistical data used the t-test. The results showed that the quality of service has a significant relationship with patient satisfaction (p-value 0,001). While the hospital cost does not have a significant relationship with satisfaction patients (p-value 0,368). Service quality has relationship with patient satisfaction. The hospital should improve dimension of service quality in order to improve patient satisfaction.